Postoperative pain management in Hospital Universiti Sains Malaysia (HUSM) - Jailani, Norzalila @ Norzakira (Universiti Sains Malaysia, 2009)
The aim of this study is to determine surgical patients' satisfaction of postoperative pain management in Hospital Universiti Sains Malaysia (HUSM). Gate Control Theory of Pain is used as a guide in this study. A descriptive cross-sectional design is used to conduct the study. The Strategic and Clinical Quality Indicators in Postoperative Pain Management (SCQIPP) questionnaires were given to patients by self administered distribution and guidelines interview. The population was all the hospitalized patients after elective major surgery in HUSM such as general, orthopedic and thoracic surgery. There were 30 patients volunteered to participate in this study which were 28 Malay and one Chinese patient. Their age is range from 18 to 60 and above years old. The findings showed that there is no items of 14 items in the SCQIPP questionnaires achieved high satisfaction of postoperative pain management (>4.5) but six items had low satisfaction of postoperative pain management which is less than 4.0. The result showed item-14 is the highest mean score and item-7 is the lowest mean score. Findings the subscales of action and trust is <4.0 while subscales of communication and environment in range 4.0 to 4.5. There is no significant different between expectation of pain after surgery and surgical patients' satisfaction of postoperative pain management, but have a correlation with satisfaction of pain relief. These postoperative pain management is a very important to reflects patient's evaluation of the action, communication, trust, environment and intervention taken by nurses and doctors in reducing pain intensity. It has important input on patients experience, recovery and health cost. Patients who experienced more pain or did not than expected after surgery does not mean they were satisfied with the pain management. However, when they satisfied with pain relief it shows that they satisfied with the postoperative pain management given.